Binder as well as preparation method and application thereof

By introducing functional groups of cyano groups and complex transition metal ions into the modified monomer of the binder, the problem of manganese ions dissolution in lithium manganese iron phosphate batteries is solved, and the cycle performance and rate performance of the battery are improved.

CN119823674APending Publication Date: 2025-04-15EVE POWER CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510031524.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During the cycle process of lithium manganese iron phosphate, manganese ions are dissolution due to the Jahn-Teller effect, which affects the circulation performance and life of the battery. At the same time, the conductivity of lithium manganese iron phosphate is poor, affecting the rate performance.

Method used

A binder is developed whose polymeric monomer includes vinylidene fluoride and a modified monomer, which introduces functional groups of cyano groups and complex transition metal ions to improve conductivity and adsorb the dissolved manganese ions.

Benefits of technology

It significantly improves the circulation performance and rate performance of lithium-ion batteries, effectively reducing the deposition of manganese ions and the internal resistance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235297290000121
    Figure BDA0005235297290000121
  • Figure FDA0005235297270000011
    Figure FDA0005235297270000011
  • Figure FDA0005235297270000012
    Figure FDA0005235297270000012
Patent Text Reader

Abstract

The invention relates to a binder as well as a preparation method and application thereof. Polymeric monomers of the binder comprise vinylidene fluoride and a modified monomer, the modified monomer includes a cyano-modified monomer containing a functional group complexed with a transition metal ion. In the modified monomer, a cyano group belongs to a strong polar group and has an electron withdrawing property, so that the conductivity of the PVDF can be remarkably improved; and functional groups complexed with transition metal ions can effectively adsorb manganese ions dissolved from the lithium manganese iron phosphate positive electrode material. The positive pole piece using the binder can effectively improve the cycle performance and the rate capability of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a binder and a preparation method and application thereof. Background Art

[0002] At present, with the increasing requirements for battery energy density, safety and cost in new energy vehicles and other fields, lithium manganese iron phosphate, as a positive electrode material with good comprehensive performance, has broad application prospects. Lithium manganese iron phosphate belongs to the olivine structure, in which PO4 3- (Phosphate ion) tetrahedron is very stable and can play a structural support role during the charge and discharge process, so that lithium manganese iron phosphate has excellent thermodynamic and kinetic stability. The addition of manganese element increases the voltage platform from about 3.6V of lithium iron phosphate to about 4.1V, which makes the energy density of lithium manganese iron phosphate higher at the same specific capacity.

[0003] However, during battery cycling, manganese (Mn) may be leached from the cathode material due to the Jahn-Teller effect. 3+ The ions are affected by the Jan-Taylor effect, causing a disproportionation reaction of manganese, so that part of the manganese is converted into Mn 2+ ions are dissolved in the electrolyte and eventually transferred to the negative electrode surface, catalyzing the side reactions on the negative electrode surface, affecting the battery's cycle performance and life. The conventional method to solve this problem is to reduce the dissolution of manganese by optimizing the material preparation process and adopting special structural designs (such as core-shell structures). However, no matter how it is optimized, the Jan-Taylor effect cannot be completely avoided, and manganese dissolution still exists. Therefore, it is necessary to develop a means to capture manganese ions to reduce the deposition of manganese ions at the negative electrode. In addition, due to the poor conductivity of lithium manganese iron phosphate itself, the rate performance of lithium manganese iron phosphate batteries is significantly affected. At this stage, the method to improve this problem is usually to add a large amount of conductive agent to the pole piece to improve the conductivity of the pole piece, but the use of a large amount of conductive agent will increase the side reactions inside the battery, thereby affecting the battery life.

[0004] Therefore, how to develop a binder for the positive electrode of lithium-ion batteries that can capture manganese ions dissolved from the positive electrode material and prevent the manganese ions from migrating and depositing on the negative electrode, thereby effectively improving the cycle performance of lithium manganese iron phosphate batteries; and can also improve the conductivity of the electrode sheet and improve the battery rate performance, has become a problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a binder and a preparation method and application thereof; the polymerized monomer of the binder includes vinylidene fluoride and a modified monomer; the modified monomer includes a cyano-modified monomer containing a functional group for complexing transition metal ions. In the modified monomer, the cyano group is a strong polar group with electron-withdrawing properties, which can significantly improve the conductivity of polyvinylidene fluoride (PVDF); the functional group for complexing transition metal ions can effectively adsorb manganese ions dissolved from lithium manganese iron phosphate positive electrode materials. The positive electrode sheet using the binder can effectively improve the cycle performance and rate performance of lithium-ion batteries.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a binder, wherein the polymerizable monomers of the binder include vinylidene fluoride and a modified monomer; the modified monomer includes a cyano-modified monomer containing a functional group for complexing transition metal ions.

[0008] The present invention introduces a cyano group with strong polarity and electron-withdrawing properties into the modified monomer, which can cause a large shift in the electron cloud of PVDF, thereby being more conducive to the delocalization and transition of electrons, thereby improving the conductivity of PVDF; the introduction of a functional group that complexes transition metal ions can effectively adsorb transition metal ions dissolved from the lithium manganese iron phosphate positive electrode material, such as manganese ions. In addition, the cyano group has a simple structure and can minimize the adverse effects on the PVDF chain segment after introduction. Therefore, the binder is applied to lithium ion batteries, solving the technical problem of how to develop a lithium ion battery with excellent cycle performance and rate performance.

[0009] Preferably, in the binder, the molar number of the structural unit based on the vinylidene fluoride is m, and the molar number of the structural unit based on the modified monomer is n, and m and n satisfy 48≤m / n≤50, for example, m / n can be 48.2, 48.5, 48.7, 49, 49.3, 49.5, 49.8, etc.

[0010] Preferably, the mass percentage of vinylidene fluoride in the polymerized monomer is 95%-98%, for example, it may be 95.5%, 96%, 96.5%, 97%, 97.5%, etc.

[0011] Preferably, the mass percentage of the modified monomer in the polymerized monomer is 2%-5%, for example, 2.5%, 3%, 3.5%, 4%, 4.5%, etc.

[0012] When the mass percentage of the modified monomer in the polymerized monomer is higher than 5%, the bonding performance of the adhesive will be reduced; when the mass percentage of the modified monomer in the polymerized monomer is lower than 2%, it cannot enhance the conductivity and adsorb transition metal ions.

[0013] Preferably, the weight average molecular weight of the binder is 1200-1600 kDa, for example, it may be 1250 kDa, 1300 kDa, 1350 kDa, 1400 kDa, 1410 kDa, 1420 kDa, 1430 kDa, 1440 kDa, 1450 kDa, 1460 kDa, 1470 kDa, 1480 kDa, 1490 kDa, 1500 kDa, 1550 kDa, etc., preferably 1400-1500 kDa.

[0014] When the weight average molecular weight of the binder is higher than 1600 kDa, the shrinkage and movement of the molecular chain are restricted during the drying or curing process after bonding, which easily leads to stress concentration and increases the internal stress. When the internal stress exceeds the bonding strength, bonding failure will occur, which ultimately reduces the capacity retention rate of the battery. When the weight average molecular weight of the binder is lower than 1200 kDa, the molecular chain is too short, there are too few sites that can provide bonding force, the bonding force is too weak, and the bonding performance is reduced.

[0015] Preferably, the functional group of the complex transition metal ion comprises any one or a combination of at least two of the following groups:

[0016] in, Indicates the attachment site of a group.

[0017] Preferably, the functional group complexing the transition metal ion includes any one or a combination of at least two of the following groups:

[0018] Preferably, the transition metal ions include manganese ions.

[0019] Preferably, the modified monomer comprises Any one or a combination of at least two.

[0020] In a second aspect, the present invention provides a method for preparing the binder according to the first aspect, the preparation method comprising the following steps:

[0021] The vinylidene fluoride and the modified monomer undergo a polymerization reaction in the presence of an initiator to obtain the binder.

[0022] Preferably, the polymerization reaction is carried out in a reactor.

[0023] Preferably, the reactor is sealed.

[0024] Preferably, the preparation method comprises the following steps: adding vinylidene fluoride and an initiator into a reaction device, and then gradually adding modified monomers thereto to carry out a polymerization reaction to obtain the binder.

[0025] The modified monomer is gradually added during the polymerization reaction, which can effectively control the uniform distribution of the structural units of the modified monomer in the polymer. If a large amount of modified monomer is added at one time, the structural units of the modified monomer will be concentrated in a certain segment of the polymer chain, while there will be no structural units of the modified monomer in other segments, thereby deteriorating the bonding performance of the binder and reducing the cycle performance and rate performance of the lithium-ion battery using the binder.

[0026] Preferably, the initiator includes any one of diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, dibenzoyl peroxide, azobisisobutyronitrile or azobisisoheptylnitrile, or a combination of at least two thereof.

[0027] Preferably, based on 100% of the mass of the vinylidene fluoride, the mass of the initiator is 0.1%-5%, for example, 0.2%, 0.5%, 1%, 2%, 3%, 4%, etc.

[0028] Preferably, the polymerization reaction is carried out in the presence of a chain transfer agent.

[0029] Preferably, the chain transfer agent includes any one of aliphatic mercaptan, trichloroethylene or ethyl acetate, or a combination of at least two thereof.

[0030] Preferably, based on 100% of the mass of the vinylidene fluoride, the mass of the chain transfer agent is 0.01%-1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, etc.

[0031] Preferably, the polymerization reaction is carried out in the presence of a solvent.

[0032] Preferably, the solvent comprises any one of carbon tetrachloride, tetrahydrofuran, cyclohexane, dichloromethane or N-methylpyrrolidone, or a combination of at least two thereof.

[0033] Preferably, the mass ratio of the solvent to the polymerizable monomer is 5:1-10:1, for example, it can be 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, etc.

[0034] Preferably, the polymerization reaction temperature is 30-50°C, for example, 33°C, 36°C, 39°C, 41°C, 42°C, 43°C, 44°C, 45°C, 48°C, etc., preferably 40-45°C.

[0035] Preferably, the polymerization reaction time is 4-10 h, for example, it can be 5 h, 6 h, 6.2 h, 6.5 h, 6.7 h, 7 h, 7.2 h, 7.5 h, 7.8 h, 8 h, 9 h, etc., preferably 6-8 h.

[0036] The polymerization reaction time is calculated from the time when vinylidene fluoride and the initiator are added.

[0037] Preferably, the polymerization reaction is carried out under the protection of protective gas.

[0038] Preferably, the protective gas comprises nitrogen.

[0039] Preferably, after the polymerization reaction is completed, the obtained binder is cleaned and impurities are removed.

[0040] In a third aspect, the present invention provides a battery electrode sheet, wherein the battery electrode sheet comprises the adhesive as described in the first aspect.

[0041] Preferably, the battery electrode is a positive electrode.

[0042] Preferably, the positive electrode sheet is made of lithium manganese iron phosphate positive electrode material.

[0043] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the battery electrode sheet as described in the third aspect.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects:

[0045] The present invention introduces a cyano group with strong polarity and electron-withdrawing properties into the modified monomer, which can cause a large shift in the electron cloud of PVDF, thereby being more conducive to the delocalization and transition of electrons, thereby improving the conductivity of PVDF; the introduction of a functional group that complexes transition metal ions can effectively adsorb transition metal ions dissolved from the lithium manganese iron phosphate positive electrode material, such as manganese ions. In addition, the cyano group has a simple structure and can minimize the adverse effects on the PVDF segment after introduction. Therefore, the lithium ion battery using the binder has excellent cycle performance and rate performance. DETAILED DESCRIPTION

[0046] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0047] The sources of the raw materials used in the embodiments of the present invention are as follows:

[0048] Manufacturer name CAS Shandong Deyi New Materials Co., Ltd. Vinylidene fluoride 75-38-7 Aladdin Biochemical Technology Co., Ltd. Azobisisobutyronitrile 78-67-1 Aladdin Biochemical Technology Co., Ltd. N-Methylpyrrolidone 872-50-4 Aladdin Biochemical Technology Co., Ltd. Ethyl acetate 141-78-6

[0049] Example 1

[0050] A binder and a preparation method thereof. The polymerizable monomers of the binder include vinylidene fluoride and a modified monomer.

[0051] The preparation method of the binder is as follows:

[0052] Add 1000g of vinylidene fluoride, 10g of initiator azobisisobutyronitrile, 5000g of solvent N-methylpyrrolidone and 5g of chain transfer agent ethyl acetate into the reactor, introduce N2 for protection, adjust the temperature at 40°C, and then gradually add 40g of modified monomer, the structure of A polymerization reaction is carried out, and the reaction time is controlled within 6 hours to obtain the binder. After the reaction is completed, the product is cleaned and impurities are removed.

[0053] Example 2

[0054] A binder and a preparation method thereof. The polymerizable monomers of the binder include vinylidene fluoride and a modified monomer.

[0055] The preparation method of the binder is as follows:

[0056] Add 1000g of vinylidene fluoride, 10g of initiator azobisisobutyronitrile, 5000g of solvent N-methylpyrrolidone and 5g of chain transfer agent ethyl acetate into the reactor, introduce N2 for protection, adjust the temperature at 40°C, and then gradually add 50g of modified monomer, the structure of A polymerization reaction is carried out, and the reaction time is controlled within 6 hours to obtain the binder. After the reaction is completed, the product is cleaned and impurities are removed.

[0057] Example 3

[0058] A binder and a preparation method thereof. The polymerizable monomers of the binder include vinylidene fluoride and a modified monomer.

[0059] The preparation method of the binder is as follows:

[0060] Add 1000g of vinylidene fluoride, 10g of initiator azobisisobutyronitrile, 5000g of solvent N-methylpyrrolidone and 5g of chain transfer agent ethyl acetate into the reactor, introduce N2 for protection, adjust the temperature at 40°C, and then gradually add 21g of modified monomer, the structure of A polymerization reaction is carried out, and the reaction time is controlled within 6 hours to obtain the binder. After the reaction is completed, the product is cleaned and impurities are removed.

[0061] Example 4

[0062] A binder and a preparation method thereof are substantially the same as those in Example 1, except that the reaction temperature in this example is 30°C.

[0063] Example 5

[0064] A binder and a preparation method thereof are substantially the same as those in Example 1, except that the reaction temperature in this example is 50°C.

[0065] Example 6

[0066] A binder and a preparation method thereof are basically the same as those in Example 1, except that the reaction time in this example is 4 hours.

[0067] Example 7

[0068] A binder and a preparation method thereof are basically the same as those in Example 1, except that the reaction time in this example is 10 hours.

[0069] Example 8

[0070] A binder and a preparation method thereof are basically the same as those in Example 1, except that the amount of the initiator in this example is 50 g.

[0071] Example 9

[0072] A binder and a preparation method thereof are basically the same as those in Example 1, except that the amount of the initiator in this example is 1 g.

[0073] Example 10

[0074] A binder and a preparation method thereof are substantially the same as those in Example 1, except that the amount of the chain transfer agent in this example is 10 g.

[0075] Embodiment 11

[0076] A binder and a preparation method thereof, which differ from Example 1 only in that the amounts of vinylidene fluoride, initiator, chain transfer agent, and modified monomer are 1000g, 15g, 10g, and 20g, respectively; the types, amounts, and preparation methods of other materials are the same as those in Example 1.

[0077] Example 12

[0078] A binder and a preparation method thereof, which are different from Example 1 only in that the reaction time of this experiment is 6.5 hours and the reaction temperature is 45°C.

[0079] Comparative Example 1

[0080] A binder and a preparation method thereof, which differs from Example 1 only in that the modified monomer is acrylonitrile; the types, amounts and preparation methods of other materials are the same as those in Example 1.

[0081] Comparative Example 2

[0082] A binder and a preparation method thereof, which differs from Example 1 only in that the modified monomer is phosphoric acid; the types, amounts and preparation methods of other materials are the same as those in Example 1.

[0083] Comparative Example 3

[0084] A binder and a preparation method thereof, which differs from Example 1 only in that no modified monomer is added; the types, amounts and preparation methods of other materials are the same as those in Example 1.

[0085] Application Example 1-12, Comparative Application Example 1-3

[0086] 1. Preparation method of positive electrode sheet: positive electrode material (lithium manganese iron phosphate) and conductive carbon black (Super P), binder, dispersant (polyvinyl pyrrolidone) are mixed in N-methylpyrrolidone (NMP) solvent at a mass ratio of 9.6:0.2:0.17:0.03, stirred evenly, and positive electrode slurry is obtained. The obtained positive electrode slurry is evenly coated on a 12 μm thick aluminum foil, and after drying, a positive electrode sheet is obtained. Among them, the binder is the binder provided in Examples 1-12 and Comparative Examples 1-3.

[0087] 2. Negative electrode sheet preparation method: Graphite, conductive carbon black (Super P), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) are mixed with deionized water in a mass ratio of 8:1:0.5:0.5 to make an electrode slurry, which is then evenly coated on a 5 μm thick copper foil and dried to obtain a negative electrode sheet.

[0088] 3. The diaphragm adopts 7+2+2 mixed coating diaphragm; the diaphragm has a three-layer structure, the middle layer is a 7μm thick PE base film, and the upper and lower sides have 2μm thick coatings, and the coatings are mixed with boehmite and PVDF glue.

[0089] The electrolyte composition is 30wt% ethylene carbonate (EC), 5wt% propylene carbonate (PC), 25wt% ethyl methyl carbonate (EMC) and 40wt% dimethyl carbonate (DMC); lithium salt in the electrolyte (50% LiFSI+50% LiPF6); the lithium salt concentration in the electrolyte is 1 mol / L.

[0090] 4. The production process includes: electrode cutting, winding / stacking, shelling, vacuum baking, liquid injection, standing, forming, insulating film pasting, etc.

[0091] Performance Testing

[0092] (1) Battery internal resistance

[0093] Use 1C discharge pulse test, duration 10s, calculation formula is:

[0094] in:

[0095] V1 is the sampling voltage at the end of static discharge and the start of discharge

[0096] V2 is the voltage at the end of discharge

[0097] I is the discharge current value

[0098] (2) Capacity retention rate

[0099] Cycle capacity retention rate test: The obtained lithium battery was fully charged and discharged at 25°C, and the cycle capacity retention rate was recorded. Full charge: At 25°C, charge at a constant current of 0.33C to the cut-off voltage (LFP3.65V, LMFP4.2V), then change to constant voltage charging with a cut-off current of 0.05C. Full discharge:

[0100] At 25℃, discharge at 1C to 2.5V.

[0101] (3) Manganese content of negative electrode sheet

[0102] 1. Digestion: Treat the negative electrode sample with a suitable digestion method, such as acid digestion, so that the manganese element therein is completely dissolved and converted into an ionic state to obtain a digested solution.

[0103] 2. Dilution and volume adjustment: Dilute the digested solution appropriately and adjust the volume to a certain volume to meet the measurement requirements of the instrument.

[0104] 3. Measurement: Use an inductively coupled plasma emission spectrometer to measure the diluted solution, select appropriate analysis lines and measurement parameters, and measure the emission light intensity of manganese.

[0105] 4. Calculation: Based on the measured light intensity, by comparing it with the calibration curve of the standard solution, the concentration of manganese ions in the sample solution is calculated, thereby obtaining the amount of manganese dissolved in the negative electrode sheet.

[0106] (4) Binder weight average molecular weight

[0107] 1. Dissolve the binder: Weigh an appropriate amount of binder sample and dissolve it in a solvent that matches the GPC column. Generally, it is necessary to completely dissolve it by stirring or ultrasound, and prepare a solution with a concentration of about 0.1%-1% (mass volume ratio) to ensure that the solution has a suitable viscosity and concentration.

[0108] 2. Filtration: Use a 0.2-0.45μm microporous filter membrane to filter the solution to remove possible insoluble matter and impurities to prevent clogging of the chromatographic column and affecting the measurement results.

[0109] 3. Injection: Inject the filtered binder sample solution into the injection port of the GPC instrument and separate under the same chromatographic conditions as the calibration, including setting appropriate mobile phase flow rate, column temperature and other parameters. The general flow rate is 0.5-1.5mL / min and the column temperature is about 30-50℃.

[0110] 4. Detection: When the sample passes through the chromatographic column, components of different molecular weights are separated in sequence according to their molecular size and flow out of the column and into the detector. The detector will convert the concentration changes of each component into electrical signals or other measurable signals. For example, the differential refractometer will measure the change in the refractive index of the solution, thereby obtaining a chromatogram of the sample, showing the peak shape and peak area at different retention times.

[0111] 5. Calculate molecular weight distribution: By integrating and analyzing each peak in the chromatogram, the molecular weight distribution of the binder can be further obtained, such as parameters such as the molecular weight distribution width index, to more comprehensively describe the molecular weight characteristics of the binder.

[0112] Test Results

[0113]

[0114] The test results show that:

[0115] (1) It can be seen from Examples 1 to 12 that the binder provided by the present invention can significantly improve the conductivity of PVDF and effectively adsorb the manganese ions dissolved from the lithium iron manganese phosphate positive electrode material. The positive electrode sheet using the binder can effectively improve the cycle performance and rate performance of the lithium ion battery. The internal resistance of the lithium ion battery containing the binder of the present invention is 2.11-2.67mΩ, the capacity retention rate is 90.2%-93.5%, and the manganese content of the negative electrode sheet is 31.0-43.5ppm.

[0116] (2) It can be seen from Example 1 and Comparative Example 1 that the present invention can reduce the manganese content of the negative electrode sheet and thereby improve the capacity retention rate by introducing a functional group that complexes transition metal ions into the modified monomer. When the functional group that complexes transition metal ions is missing, the manganese content of the negative electrode sheet increases and the capacity retention rate decreases.

[0117] It can be seen from Example 1 and Comparative Example 2 that the present invention can reduce the internal resistance of the battery by introducing cyano groups into the modified monomer, while when the cyano groups are missing, the internal resistance of the battery increases.

[0118] It can be seen from Example 1 and Comparative Example 3 that if no modified monomer is added, the internal resistance of the battery increases, the capacity retention rate decreases, and the manganese content of the negative electrode increases.

[0119] (3) It can be seen from Example 1 and Examples 11 and 12 that the present invention can obtain a higher capacity retention rate by further controlling the weight average molecular weight of the binder.

[0120] In summary, the present invention improves the conductivity of PVDF by introducing cyano groups into the modified monomers, and effectively adsorbs the transition metal ions dissolved from the lithium manganese iron phosphate positive electrode material by introducing functional groups for complexing transition metal ions. The lithium ion battery using the binder has excellent cycle performance and rate performance.

[0121] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A binder, characterized in that: The polymerizable monomers of the binder include vinylidene fluoride and a modified monomer; The modified monomer includes a cyano-modified monomer containing a functional group for complexing transition metal ions.

2. The adhesive according to claim 1, characterized in that In the binder, the number of moles of the structural unit based on the vinylidene fluoride is m, the number of moles of the structural unit based on the modified monomer is n, and m and n satisfy 48≤m / n≤50.

3. The adhesive according to claim 1 or 2, characterized in that: The mass percentage of vinylidene fluoride in the polymerized monomer is 95%-98%; Preferably, the mass percentage of the modified monomer in the polymerized monomer is 2%-5%; Preferably, the weight average molecular weight of the binder is 1200-1600 kDa, preferably 1400-1500 kDa.

4. The adhesive according to any one of claims 1 to 3, characterized in that: The functional group of the complexed transition metal ion includes any one or a combination of at least two of the following groups: in, Indicates the attachment site of the group; Preferably, the functional group complexing the transition metal ion includes any one or a combination of at least two of the following groups: Preferably, the transition metal ions include manganese ions.

5. The adhesive according to any one of claims 1 to 4, characterized in that: The modified monomer includes Any one or a combination of at least two.

6. A method for preparing the adhesive according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The vinylidene fluoride and the modified monomer undergo a polymerization reaction in the presence of an initiator to obtain the binder.

7. The preparation method according to claim 6, characterized in that: The initiator includes any one of diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, dibenzoyl peroxide, azobisisobutyronitrile or azobisisoheptylnitrile or a combination of at least two thereof; Preferably, based on 100% of the mass of the vinylidene fluoride, the mass of the initiator is 0.1%-5%; Preferably, the polymerization reaction is carried out in the presence of a chain transfer agent; Preferably, the chain transfer agent comprises any one or a combination of at least two of aliphatic mercaptan, trichloroethylene or ethyl acetate; Preferably, based on 100% of the mass of the vinylidene fluoride, the mass of the chain transfer agent is 0.01%-1%; Preferably, the polymerization reaction is carried out in the presence of a solvent; Preferably, the solvent comprises any one or a combination of at least two of carbon tetrachloride, tetrahydrofuran, cyclohexane, dichloromethane or N-methylpyrrolidone; Preferably, the mass ratio of the solvent to the polymerization monomer is 5:1-10:

1.

8. The preparation method according to claim 6 or 7, characterized in that: The polymerization reaction temperature is 30-50°C, preferably 40-45°C; Preferably, the polymerization reaction time is 4-10h, preferably 6-8h; Preferably, the polymerization reaction is carried out under the protection of protective gas; Preferably, the protective gas comprises nitrogen.

9. A battery pole piece, characterized in that: The battery pole piece comprises the adhesive according to any one of claims 1 to 5; Preferably, the battery electrode is a positive electrode.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the battery pole piece as claimed in claim 9.

Citation Information

Cited By

  • High-voltage positive electrode binder with multi-function synergy and preparation method and application thereof

    CN121699043A